Rancangan Strategi Manajemen Kinerja PT XYZ Tahun 2022-2024: Performance Management Strategy Design PT XYZ 2022-2024 - Sitorus, Benny; Wendra (Jurnal Aplikasi Bisnis dan Manajemen, 2023)
Performance management is a process carried out by the organization to ensure that the organization's business goals are aligned with the goals of the work units and individuals within it. The purpose of this study is to map business typologies, performance management direction and policies, the gap between theory and application performance management at PT XYZ, and strategy and implementation plans for company’s performance management. This research is an applied research with a descriptive qualitative approaches. Methods of data collection were carried out through surveys, interviews with 6 (six) managers and conducting studies on company performance management documents. Survey results were analyzed by comparing the mean value with predetermined assessment standards. Interview data were analyzed by using the content analysis method. The results of the research show that PT XYZ performance management needs to be improved starting from the stages of planning, implementation, assessment, up to performance rewarding. This study also compiles guidelines for the implementation of performance management plans by means of communication, appeals processes, training programs, trials, monitoring-evaluation and online implementation. The results of the performance management system design and its implementation plan need to be carried out by the management team and all employees on an ongoing basis with due regard to communication, appeals processes, training programs, trials, monitoring, evaluation and implemented online. Keywords: applied research, business strategy, human resource management, perfomance management, qualitative and quantitative research